A study on the performance measurement of the service employee in banking industries: securities services of Scope International (M) Sdn Bhd / Tengku Ahmad Faris Tengku Ismail - Tengku Ismail, Tengku Ahmad Faris (2010)
The study highlights the measurement of employee’s performance in the banking sector such as Scope International (M) Sdn Bhd in ensuring the quality and efficiency of the employees in order to convince the customer about the capability of the bank to provide services as their promise. The scope of this study is focusing on how the organization measures the performance of their service employees in order to maintain and increase the productivity and at the same time to generate the competent employees, and ultimately improves the quality of their services. These study however, focusing only on Securities Services Operations instead of studying for the whole organization. In this study the researcher was studied and analyzes the data related for year 2009. Measurement of the employee’s performance in service sectors can be differing from the measurement of performance for employees who work in manufacturing or industrial sectors. For instance, in manufacturing industry, employees’ performance can be measured by looking at the number of products that can be produce in a certain period of time. So, this situation explains that the best practices of performance measurement is needed in enhancing the quality of services and at the same time can improve the performance of the employees in providing the service using the right way in order to ensure customer satisfaction.